MEMBANGUN MINAT BELAJAR MATEMATIKA MELALUI BIMBEL UNTUK SISWA SD Negeri No.067249 MEDAN - Mahmud. S, Ronald; Nazaruddin, Ilham (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
Smart and competitive generations are mainly produced by quality education. To improve the quality of human resources, non-formal and informal education are as important as formal education. Evaluating the impact of the free mathematics tutoring program implemented at SDN 067249 Medan is the goal of this community service project. This program aims to increase learning motivation and enable students of SDN 067249 Medan to understand the mathematics curriculum. Five times a week at the KKN Post, professors and students of STKIP AMAL BAKTI provide free education as part of the implementation approach. Although there are certain limitations such as implementation time and specific student demands, the results show a marked increase in student motivation and understanding and there is potential in this program